2014
DOI: 10.1111/cen.12629
|View full text |Cite
|
Sign up to set email alerts
|

US not bright but right method of thyroid volume estimation even in large and substernal extended goitres. Comparison of US and three methods of CT thyroid evaluation – prospective study

Abstract: US examination is sufficient for epidemiological studies, radioiodine activity calculation and goitre size assessment in everyday medical practice. Neither initial size of the goitre nor its substernal extension affects US assessment precision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
(78 reference statements)
2
12
0
Order By: Relevance
“…U ltrasonography is widely used in clinical practice as the most reliable method to determine the volume (1,2) and structure of the thyroid gland. The volume of the thyroid is influenced by age, gender, body mass index (BMI), lean body mass, iodine intake, and genetic factors (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…U ltrasonography is widely used in clinical practice as the most reliable method to determine the volume (1,2) and structure of the thyroid gland. The volume of the thyroid is influenced by age, gender, body mass index (BMI), lean body mass, iodine intake, and genetic factors (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [24] have shown that thyroid volume measured by ultrasound is the preferred indicator in epidemiological studies and monitoring of iodine deficiency disorders. Nevertheless, thyroid volume measured by ultrasound needs reliable reference intervals for normal thyroid volume from iodine-sufficient populations.…”
Section: Introductionmentioning
confidence: 99%
“…No statistically significant difference was observed between US and CT volumetric evaluation either before the treatment (H = 1.74; p = 0.6291) or afterwards (H = 1.09; p = 0.7786). Additionally, using Bland-Atman plots, we assessed previously that in volumetric thyroid measurements US is a comparable method to CT; therefore, in this study US examination was established as a reference method [9].…”
Section: Resultsmentioning
confidence: 99%